Phylogeographic patterns of Cyphocharax from trans-Andean rivers and northward expansion to lower Central America (Teleostei, Curimatidae) - Melo, Bruno F.; Conde-Saldaña, Cristhian C.; Villa-Navarro, Francisco A.; McMahan, Caleb D.; Oliveira, Claudio [UNESP] (Wiley, 2024)
Phylogenetic analyses of mitochondrial and nuclear data of 31 specimens of Cyphocharax from trans-Andean rivers support the presence of one lineage of Cyphocharax aspilos in Lago Maracaibo and three cryptic lineages of Cyphocharax magdalenae: (1) Cauca-Magdalena and Ranchería, (2) León and Atrato, and (3) Chucunaque-Tuira, Santa María, and Chiriquí basins of Central America. Results suggest that the Serranía del Perijá facilitated Late Miocene cladogenetic events, whereas post-Isthmian C. magdalenae expansion was enabled by gene flow across the lower Magdalena valley and Central American lowlands. Time-calibrated phylogenetics indicate that the C. magdalenae colonized lower Central America in the Pliocene (3.7 MYA; Ma), the divergence Atrato-Magdalena occurred in Late Pliocene (3.0 Ma) and the split Ranchería-Magdalena during the Middle Pleistocene (1.3 Ma). Updated geographic distribution data support the hypothesis that the Cordillera de Talamanca functions as a barrier to northward expansion of C. magdalenae in Central America.
Keywords: Characiformes; Magdalena; Maracaibo; Ostariophysi; Serranía del Perijá; Talamanca